The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1128/aem.00434-18
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation in Experimental Ulcerative Colitis Reveals Associated Gut Microbial and Host Metabolic Reprogramming

Abstract: Fecal microbiota transplantation (FMT) is gaining attention for the treatment of ulcerative colitis (UC). Data from individual case studies have suggested that FMT may be beneficial for UC, but the detailed microbial and molecular basis remains unknown. Here, we employ 16S rRNA gene sequencing and metabolomics to investigate the influence of FMT on gut microbial community composition and host metabolism in the dextran sulfate sodium-induced UC rat model. The findings from this pilot study suggest that FMT from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…Microbiome data were analyzed according to our previous study [35], with minor modifications. Briefly, data processing, normalization, scaling, and multivariate analyses were performed using the R package MetaboAnalystR [36].…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…Microbiome data were analyzed according to our previous study [35], with minor modifications. Briefly, data processing, normalization, scaling, and multivariate analyses were performed using the R package MetaboAnalystR [36].…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…In particular, the Desulfovibrio and Clostridium genera have been closely linked to UC [6]. Thus, the development of UC is closely related to changes in the intestinal flora [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that hippuric acid decreased in the normal rats but was restored to normal levels at day 6 and 7, and further found that the changes induced by FMT correlated with the genera Oscillospira and Dehalobacterium and the families Bacillaceae and Exiguobacteraceae. 52 Importantly it has been shown that hippuric acid is reduced in CD and UC due to gut microbial metabolism; this therefore suggests that FMT can alter the gut microbiome to change the metabolic drivers of disease states. 53 Further supporting this concept was a study on pigs, where it was noted that FMT resulted in significant increases of the typical microbiotaderived tryptophan catabolite indole-3-acetic acid in the colonic lumen, 54 suggesting that tryptophan metabolites may be important actors in the efficacy of FMT.…”
Section: Shortmentioning
confidence: 99%